Journey of kenaf in Malaysia: a review - Basri, Mohd Hadi Akbar; Abdu, Arifin; Junejo, Nasima; Abdul Hamid, Hazandy; Ahmed, Khalil (Academic Journals, 2014)
Kenaf is an industrial crop with high potential for cultivation in a tropical climate. It is a source of raw material for fiber-based industries and paper production. Considerable research has been conducted to explore its adaptability and utilization in Malaysia since 2000, under the supervision of governmental and private organizations. A number of technologies and expertise among researchers have been developed to enhance kenaf production in Malaysia. However, international documentation of the research is limited, which is important for rectification to provide a comprehensive knowledge base for all tropical and subtropical countries. The main objective of this review is to provide an overview of the results of Malaysian research on kenaf. In addition, the past, present and likely future trends in kenaf research in Malaysia as a representative tropical region are summarized.